'Fading of the temperature‐growth coupling' in treeline trees reflects a conceptual bias. (21st June 2021) - Körner, Christian
Abstract : The global treeline phenomenon follows a common seasonal mean temperature (isotherm) of about 6°C. When the isotherm moves upslope because of rapid climatic warming, trees are left behind and are absent from the climatic tree limit. This commentary recalls the discrepancy between the actual uppermost position of trees and the potential (climatic) treeline. Temperature‐based models can predict the potential treeline only (comment to Camarero et al., Global Change Biology, 27, 1879–1889, 2021). The photograph shows a treeline situation in SW New Zealand.